Exploitation and Domination in Marx's Thought. Issue 4 (2nd October 2019) - Terray, Emmanuel; Serrano, Joseph
Abstract : In traditional Marxism, domination and exploitation constitute two distinct processes that, in turn, belong to two different spheres of social reality. This essay attempts to show that within the capitalist mode of production, like those modes that preceded it, domination is in fact the primary relation and is located at the very base of relations of exploitation. Indeed, exploitation only occurs when a minority determines the use of surplus labor. Moreover, the degree of exploitation depends on the level of mastery over the labor force, which is in turn an effect of the balance of forces between the worker and the owner of the means of production.